A highly secured and streamlined cloud collaborative editing scheme along with an efficient user revocation in cloud computing. (18th October 2019) - Eswara Narayanan, Munisamy; Muthukumar, Balasundaram
Summary: These days with the expanded fame of cloud computing, the interest for cloud‐based collaborative editing service is rising. The encryption method is utilized to ensure and secure the data, during the collaborative editing process. In the encryption process, the cloud requires more time to work the collaborative editing. This paper proposes an efficient scheme for reducing the encryption burden over the cooperative users, as the possibilities of cooperative users read and write data by means of any gadget. In the proposed scheme, the encrypted file sent by the data owner is split into smaller segments and stored in the cloud by the cloud service provider (CSP) along with specific tags. Once the cooperative user receives and decrypts the file from the CSP, it modifies and encrypts only the modified segment and resends to the CSP. The CSP after verifying the signature replace the original file segment in the cloud with the modified segment based on the tag information. The scheme that is put forward is performed based on the modified ciphertext‐policy hierarchical attribute–based encryption, and the security process is done based on the attribute‐based signature schemes. This work employs a proficient attribute updating method to accomplish the dynamic change of users' attributes, consisting granting new attributes, revoking previous attributes, and regranting formerly revoked attributes. A writer's attributes and keys have been revoked, and the stale information cannot be written.